Ultrasonic rolling composite strengthening method for preparing gradient nano lamellar structure

Through the ultrasonic rolling composite strengthening method, the ultrasonic parameters and surface reprocessing are adjusted, which solves the problem that the ultrasonic rolling preparation gradient nanolayer structure is prone to surface defects, and significantly improves the fatigue performance of metal materials.

CN119194053AActive Publication Date: 2024-12-27EAST CHINA UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411329981.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Ultrasonic rolling surface strengthening preparation of gradient nanolayer structures is prone to surface defects and affect fatigue performance.

Method used

Using ultrasonic rolling composite reinforcement method, by installing metal material samples and ultrasonic rolling devices on CNC lathes, adjusting the ultrasonic frequency and amplitude, performing step by step ultrasonic rolling processing, and lubrication and cooling during the processing process, using optical The microstructure was observed by a microscope, the processing parameters were adjusted to reach the preset strain rate threshold, and the surface was reprocessed to prepare the gradient nanolayer structure.

Benefits of technology

It effectively improves the fatigue performance of metal materials, reduces surface roughness, and enhances the anti-fatigue characteristics of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194053A_ABST
    Figure CN119194053A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrasonic rolling composite strengthening method for preparing a gradient nano lamellar structure, and relates to the technical field of metal material machining, the method comprises the steps that a metal material sample and an ultrasonic rolling strengthening device are installed on a lathe, and ultrasonic rolling machining parameters are set; starting the lathe to perform step-by-step ultrasonic rolling processing on the surface of the metal material sample to obtain a metal material sample with a gradient nano lamellar structure; observing the axial section of the gradient nano lamellar structure by using a microscope to obtain a microstructure image, determining the strain rate of the gradient nano lamellar structure, and judging whether the strain rate exceeds a preset strain rate threshold value or not; if yes, carrying out surface retreatment on the gradient nano lamellar structure to obtain the prepared gradient nano lamellar structure; and if not, the corresponding ultrasonic rolling machining parameters are adjusted until the strain rate of the gradient nanometer lamellar structure exceeds the preset strain rate threshold value. The fatigue performance of the gradient nano lamellar structure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal material processing, and in particular to an ultrasonic rolling composite strengthening method for preparing a gradient nano-laminated structure. Background Art

[0002] With the rapid development of strategic emerging industries such as the new generation of new energy and high-end equipment manufacturing, there is a more urgent need to improve the performance of metal materials. The failure forms of metal materials in different fields mainly include corrosion, wear and fatigue failure, among which fatigue failure is the most common. Fatigue failure refers to the process in which parts are subjected to alternating loads such as heat and force, and the damage continues to accumulate until they suddenly break. Therefore, the improvement of the fatigue resistance of metal materials has become a key issue in current research.

[0003] In engineering, fatigue failure of parts often starts from the surface of the material. This is because when there are some defects or crack-like cracks on the surface of the parts, a large stress concentration will be formed. Under cyclic loads, cracks are likely to initiate from defects with high stress concentration, and expand on this basis until fatigue failure occurs. Therefore, various surface strengthening processes are usually selected in engineering to improve the surface quality of parts and components and improve their fatigue resistance.

[0004] At present, common surface strengthening methods include shot peening, laser shock strengthening and ultrasonic rolling strengthening, etc. Among them, the ultrasonic rolling surface strengthening method involves more complex process parameters. Compared with the traditional rolling method, the ultrasonic impact energy of the ultrasonic rolling method is larger, which will cause serious plastic deformation of the strengthening area and easily cause surface roughness. Summary of the invention

[0005] The purpose of this application is to provide an ultrasonic rolling composite strengthening method, device, equipment, medium and product for preparing gradient nano-lamellar structures, so as to solve the problem that ultrasonic rolling surface strengthening to prepare gradient nano-lamellar structures is prone to surface defects and thus affects fatigue performance.

[0006] To achieve the above objectives, this application provides the following solutions:

[0007] The present application provides an ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure, and the ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure comprises:

[0008] The current metal material sample and the ultrasonic rolling strengthening device are respectively installed on a CNC lathe, and ultrasonic rolling processing parameters are set; the ultrasonic rolling processing parameters include the static pressure of the ultrasonic rolling strengthening device, the feed speed of the CNC lathe, and the rotation speed of the CNC lathe;

[0009] Starting the ultrasonic generator, and adjusting the frequency of the ultrasonic generator to a preset frequency, and adjusting the amplitude of the ultrasonic generator to a preset amplitude;

[0010] Starting a numerically controlled lathe to perform ultrasonic rolling processing on the surface of the current metal material sample step by step, and lubricating and cooling the surface of the current metal material sample during the ultrasonic rolling processing step by step, so as to obtain a metal material sample with a gradient nano-lamellar structure;

[0011] The axial cross section of the gradient nano-lamellar structure is observed by using an optical microscope to obtain a microstructure image of the axial cross section of the gradient nano-lamellar structure;

[0012] Determine the strain rate of the gradient nano-lamellar structure based on the microstructure image of the axial cross section of the gradient nano-lamellar structure, and judge whether the strain rate of the gradient nano-lamellar structure is greater than or equal to a preset strain rate threshold;

[0013] If yes, the gradient nano-lamellar structure is subjected to surface reprocessing to obtain a prepared gradient nano-lamellar structure;

[0014] If not, the corresponding ultrasonic rolling processing parameters are adjusted until the strain rate of the gradient nano-lamellar structure is greater than or equal to the preset strain rate threshold, and the gradient nano-lamellar structure is surface-processed to obtain a prepared gradient nano-lamellar structure.

[0015] Optionally, the preset frequency is 20 kHz, and the preset amplitude is 16 μm.

[0016] Optionally, the surface of the current metal material sample is subjected to ultrasonic rolling processing step by step, specifically including:

[0017] The surface of the current metal material sample is subjected to step-by-step ultrasonic rolling processing using a first preset static pressure threshold and a second preset static pressure threshold in sequence; wherein the second preset static pressure threshold is greater than the first preset static pressure threshold.

[0018] Optionally, the surface of the current metal material sample is subjected to multiple step-by-step ultrasonic rolling processes.

[0019] Optionally, the number of step-by-step ultrasonic rolling processes is 4.

[0020] Optionally, the preset strain rate threshold is 10 3 s -1 .

[0021] Optionally, determining the strain rate of the gradient nano-lamellar structure based on the microstructure image of the axial cross section of the gradient nano-lamellar structure specifically includes:

[0022] Based on the microstructure image of the axial cross section of the gradient nanolamellar structure, the rheological curve is drawn;

[0023] Based on the rheological curve, fitting to obtain a first operating condition parameter and a second operating condition parameter;

[0024] Determining the relationship between the rheological displacement field and the depth of the gradient nano-lamellar structure based on the first operating condition parameter and the second operating condition parameter;

[0025] Based on the relationship between the rheological displacement field and depth of the gradient nanolamellar structure, the shear displacement field of the gradient nanolamellar structure is determined;

[0026] Based on the shear displacement field of the gradient nanolamellar structure, the strain rate of the gradient nanolamellar structure is determined.

[0027] Optionally, the relationship between the rheological displacement field and the depth of the gradient nanolamellar structure is expressed as:

[0028] y(x)=y s exp(-kx);

[0029] Where x is the depth of any point on the rheological curve of the gradient nanolamellar structure; y is the rheological displacement of any point on the rheological curve of the gradient nanolamellar structure; y s is the first operating condition parameter; k is the second operating condition parameter;

[0030] The expression of the shear displacement field of the gradient nanolamellar structure is:

[0031] γ(x)=y s kexp(kx);

[0032] Where γ(x) is the shear displacement field of the gradient nanolamellar structure;

[0033] The expression of strain rate of gradient nanolamellar structure is:

[0034]

[0035] in, is the strain rate of the gradient nanolamellar structure; R is the diameter of the metal material sample; v1 is the rotation speed of the CNC lathe.

[0036] Optionally, the surface reprocessing methods for the gradient nano-lamellar structure at the moment include tumbling, vibration blasting and tumbling.

[0037] Optionally, tapping oil is used as a lubricating medium and a cooling medium to lubricate and cool the surface of the current metal material sample during the step-by-step ultrasonic rolling process.

[0038] Optionally, the metal material sample is one of titanium, nickel, copper, iron, and aluminum, or an alloy formed by several of them.

[0039] According to the specific embodiments provided in this application, this application discloses the following technical effects:

[0040] The present application discloses an ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure. The metal material sample with a gradient nano-lamellar structure is obtained by ultrasonic rolling the surface of the metal material sample, and an optical microscope is used to obtain a microstructure image of the axial section of the gradient nano-lamellar structure. Based on the microstructure image of the axial section of the gradient nano-lamellar structure, the strain rate of the gradient nano-lamellar structure is determined, and it is judged whether the strain rate meets the requirements. If not, the corresponding ultrasonic rolling processing parameters are changed, and the metal material sample with the gradient nano-lamellar structure is ultrasonically rolled again until the strain rate meets the requirements, and the gradient nano-lamellar structure is surface-reprocessed to obtain a prepared gradient nano-lamellar structure. The gradient nano-lamellar structure obtained when the strain rate meets the requirements has good fatigue performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 A schematic diagram of a process flow of an ultrasonic rolling composite strengthening method for preparing a gradient nano-laminated structure provided in one embodiment of the present application;

[0043] Figure 2 A schematic diagram of sampling a metal material sample provided in one embodiment of the present application;

[0044] Figure 3 A microstructure image of an axial cross section of an industrial pure titanium rod-shaped sample provided in one embodiment of the present application;

[0045] Figure 4 A schematic diagram of a transmission electron microscope photograph of an industrial pure titanium rod sample after ultrasonic rolling provided in one embodiment of the present application;

[0046] Figure 5 Another schematic diagram of a transmission electron microscope photograph of an industrial pure titanium rod sample after ultrasonic rolling provided in one embodiment of the present application;

[0047] Figure 6 This is a schematic diagram of the SN fatigue curve of an industrial pure titanium rod specimen under different surface strengthening methods provided in one embodiment of the present application. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0049] Ultrasonic rolling strengthening technology combines the advantages of static rolling and ultrasonic impact. It uses ultrasonic vibration to generate a huge impact while making the working ball roll on the surface, so that it can effectively introduce residual compressive stress, form a surface gradient layer, and reduce the surface roughness as much as possible. In addition, this technology also has the advantages of easy operation, low installation and maintenance costs, and good process controllability. High strain rate and large static pressure are the formation conditions for preparing gradient nano-lamellar structures, and they will also lead to more surface defects. These factors affect the fatigue performance of the material after surface strengthening, and surface reprocessing methods are needed to improve the fatigue performance of the material after surface strengthening. In view of the problem that the preparation of gradient nano-lamellar structures by ultrasonic rolling surface strengthening is prone to surface defects that affect fatigue performance, this application proposes an ultrasonic rolling composite strengthening method for preparing gradient nano-lamellar structures, which enhances the surface strengthening effect of the material and further improves the fatigue performance of the material.

[0050] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0051] In an exemplary embodiment, Figure 1 As shown, an ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure is provided, comprising the following steps S1 to S7. Among them:

[0052] Step S1, respectively install the current metal material sample and the ultrasonic rolling strengthening device on a CNC lathe, and set ultrasonic rolling processing parameters, including the static pressure of the ultrasonic rolling strengthening device, the feed speed of the CNC lathe, and the rotation speed of the CNC lathe.

[0053] Specifically, the current metal material sample is mounted on a rotatable spindle of a CNC lathe, a working ball is mounted on a feed shaft of the CNC lathe, the working ball of the ultrasonic rolling device is aligned with the current metal material sample, ultrasonic waves are converted into mechanical vibrations of the working ball, and a gradient nano-lamellar structure is formed on the current metal material sample through the rotation of the spindle and the movement of the feed shaft. Preferably, the working ball is a YG6 tungsten steel ball; and the metal material sample is a rod-shaped sample.

[0054] Step S2, start the ultrasonic generator, and adjust the frequency of the ultrasonic generator to a preset frequency, and adjust the amplitude of the ultrasonic generator to a preset amplitude. The function of the ultrasonic wave is to ensure a smooth surface. The higher the frequency, the better the surface quality. However, if the frequency is too high, the ultrasonic frequency mechanical vibration of the working ball will be unstable.

[0055] As an optional implementation, the preset frequency is 20 kHz, and the preset amplitude is 16 μm.

[0056] Step S3, start the CNC lathe, perform ultrasonic rolling processing on the surface of the current metal material sample step by step, and continuously lubricate and cool the surface of the current metal material sample during the ultrasonic rolling processing, so as to obtain a metal material sample with a gradient nano-lamellar structure. The specific working principle is: under the conditions of a certain static pressure and feed speed, the processing head applies mechanical vibration of ultrasonic frequency to the surface of the current metal material sample, so that the material surface produces plastic deformation.

[0057] As an optional implementation, the surface of the current metal material sample is subjected to ultrasonic rolling processing step by step, specifically including:

[0058] The surface of the current metal material sample is subjected to step-by-step ultrasonic rolling processing using a first preset static pressure threshold and a second preset static pressure threshold in sequence; wherein the second preset static pressure threshold is greater than the first preset static pressure threshold.

[0059] Among them, the step-by-step ultrasonic rolling process is to first use a relatively small static pressure (equal to the first preset static pressure threshold) to roll the surface of the metal material sample, and then apply a target static pressure (equal to the second preset static pressure threshold) to perform ultrasonic rolling on the surface of the metal material sample. By first rolling the surface of the metal material sample with a relatively small static pressure to achieve the effect of hardening the surface, and then applying a relatively large static pressure for ultrasonic rolling, it is avoided that the applied load is too large at once, thereby causing surface defects to the material.

[0060] As an optional implementation, the surface of the current metal material sample is subjected to multiple step-by-step ultrasonic rolling processes; preferably, the number of step-by-step ultrasonic rolling processes is 4. The number of rolling processes is one of the most important parameters to ensure surface smoothness. If the number is too small, the gradient nano-lamellar structure cannot be formed, and if the number is too large, the accumulated plasticity will be excessive and cracks and other surface defects will be generated. After experimental verification, in this embodiment, when the number of step-by-step ultrasonic rolling processes is 4, the fatigue performance, thickness and other parameters of the prepared gradient nano-lamellar structure are optimal.

[0061] Step S4, observing the axial cross section of the gradient nano-lamellar structure using an optical microscope to obtain a microstructure image of the axial cross section of the gradient nano-lamellar structure.

[0062] Specifically, after the surface of the current metal material sample is subjected to step-by-step ultrasonic rolling processing, a gradient nano-lamellar structure is obtained, and an inverted Zeiss optical microscope is used to observe the axial section of the gradient nano-lamellar structure in the depth direction. First, the sampling position of the metallographic sample is axial section sampling. The sampling schematic diagram of the current metal material sample is as follows: Figure 2 As shown. Sampling is carried out by wire cutting, that is, wire cutting is performed on metal material samples with gradient nano-lamellar structures to obtain observation sections. During cutting, in order to reduce the influence of high temperature on the structure and residual stress during wire cutting, a small current is used for cutting; then, the observation section is polished with 400 mesh, 800 mesh, 1200 mesh, 2000 mesh and 4000 mesh sandpaper in turn, and polished with a homemade alumina suspension; secondly, the polished observation section is corroded, and the metallographic etching liquid uses a solution of HF:HNO3:H2O=1:2:17, and the corrosion time is 20 seconds; finally, it is rinsed with alcohol, blown dry, and the observation section of the gradient nano-lamellar structure is observed under an optical microscope at a suitable magnification, and the following can be obtained. Figure 3 Microstructure image of the axial cross-section of the gradient nanolamellar structure shown.

[0063] Step S5, determining the strain rate of the gradient nano-lamellar structure based on the microstructure image of the axial cross-section of the gradient nano-lamellar structure, and judging whether the strain rate of the gradient nano-lamellar structure is greater than or equal to a preset strain rate threshold.

[0064] As an optional implementation, in step S5, the strain rate of the gradient nano-lamellar structure is determined based on the microstructure image of the axial cross section of the gradient nano-lamellar structure, specifically including:

[0065] Step S51, drawing a rheological curve based on the microstructure image of the axial cross section of the gradient nano-lamellar structure.

[0066] Step S52: fitting the first operating condition parameter and the second operating condition parameter based on the rheological curve.

[0067] Step S53, based on the first operating condition parameter and the second operating condition parameter, determine the relationship between the rheological displacement field and the depth of the gradient nano-lamellar structure. The expression for the relationship between the rheological displacement field and the depth of the gradient nano-lamellar structure is:

[0068] y(x)=y s exp(-kx)(1)

[0069] Where x is the depth of any point on the rheological curve of the gradient nanolamellar structure; y is the rheological displacement of any point on the rheological curve of the gradient nanolamellar structure; y sis the first working condition parameter; k is the second working condition parameter. Among them, a point on the surface of the microstructure image of the axial section of the gradient nanolamellar structure is selected as the origin, the tangent direction along the surface is set as the y axis, and the direction pointing to the center of the circle is set as the x axis. An xy coordinate system is established, and the coordinates of the points on the rheological curve are obtained based on this coordinate system. The parameter y is fitted based on the coordinates (x and y values) of multiple points on the rheological curve s and k.

[0070] Step S54, based on the relationship between the rheological displacement field and the depth of the gradient nano-lamellar structure, the shear displacement field of the gradient nano-lamellar structure is determined. The expression of the shear displacement field of the gradient nano-lamellar structure is:

[0071]

[0072] Where γ(x) is the shear displacement field of the gradient nanolamellar structure.

[0073] Step S55, based on the shear displacement field of the gradient nano-lamellar structure, determine the strain rate of the gradient nano-lamellar structure. The strain rate of the gradient nano-lamellar structure is expressed as:

[0074]

[0075] in, is the strain rate of the gradient nanolamellar structure; R is the diameter of the metal material sample; v1 is the rotation speed of the CNC lathe.

[0076] According to formula (3), when the diameter R of the metal material sample is constant, the CNC lathe speed v1 and the parameter k directly affect the strain rate, and the parameter k is determined by the static pressure and the CNC lathe feed speed. Therefore, the specific static pressure, CNC lathe speed and CNC lathe feed speed of the ultrasonic rolling process in this embodiment are determined by the ultrasonic rolling material.

[0077] As an optional implementation, in step S5, the preset strain rate threshold is 10 3 s -1 .

[0078] Specifically, the preparation of gradient nano-lamellar structures is related to the strain rate in the processing technology. Only high strain rate and high static pressure can produce thick and uniform gradient nano-lamellar structures.

[0079] Step S6: If yes, the gradient nano-lamellar structure is subjected to surface reprocessing to obtain a prepared gradient nano-lamellar structure.

[0080] Step S7, if not, adjust the corresponding ultrasonic rolling processing parameters until the strain rate of the gradient nano-lamellar structure is greater than or equal to the preset strain rate threshold, and perform surface reprocessing on the gradient nano-lamellar structure to obtain the prepared gradient nano-lamellar structure. In other words, the metal material sample with the gradient nano-lamellar structure is used as the current metal material sample, and return to step S3 "start the CNC lathe and perform step-by-step ultrasonic rolling processing on the surface of the current metal material sample" until the strain rate of the gradient nano-lamellar structure is greater than or equal to the preset strain rate threshold.

[0081] As an optional implementation, the surface reprocessing methods for the gradient nano-lamellar structure at the moment include tumbling, vibration tumbling and tumbling.

[0082] As an optional implementation, tapping oil is used as a lubricating medium and a cooling medium to continuously lubricate and cool the surface of the current metal material sample during the step-by-step ultrasonic rolling process. Compared with lubricating media such as diesel and engine oil, tapping oil has a stronger lubricating effect and extreme pressure and anti-wear properties. At the same time, it has outstanding cooling performance and good penetration performance, which can effectively improve the surface roughness of metal material samples.

[0083] As an optional implementation, the metal material sample is one of titanium, nickel, copper, iron, and aluminum, or an alloy formed by several of them.

[0084] The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure of the present application is further explained below by taking the application of the ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure of the present application to industrial pure titanium as an example.

[0085] Commercially pure titanium (CP-Ti) has the advantages of non-toxicity, low density, high specific strength, strong corrosion resistance and excellent biocompatibility, and has been widely used in aerospace, petrochemical, transportation and biomedicine. However, commercially pure titanium is a difficult-to-deform material, its strength is lower than that of titanium alloy, and its fatigue resistance is poor, which limits its in-depth application in the field of materials to a certain extent. Therefore, the ultrasonic rolling composite strengthening method used in this application for preparing a gradient nano-lamellar structure is used to optimize the fatigue resistance of commercially pure titanium, and the specific steps are as follows:

[0086] 1) Install the industrial pure titanium sample and the ultrasonic rolling device on the CNC lathe respectively, and set the ultrasonic rolling processing parameters. Specifically, the industrial pure titanium sample is installed at the output end of the rotation system of the CNC lathe, the ultrasonic rolling device is installed at the clamping end of the automatic feeding system of the CNC lathe, and the working ball is aligned with the sample. The industrial pure titanium sample is installed on the rotatable spindle of the CNC lathe, so that the rotation of the spindle drives the rotation of the sample, and the working ball is installed on the axially feedable feed shaft of the CNC lathe, so that the axial feeding of the working ball is driven by the movement of the feed shaft. Preferably, before the industrial pure titanium sample is installed on the spindle, the surface to be processed of the industrial pure titanium sample is fine-turned.

[0087] 2) Start the ultrasonic generator, adjust the frequency of the ultrasonic generator to 20kHz, adjust the amplitude of the ultrasonic generator to 16μm, convert the ultrasonic wave into the ultrasonic frequency mechanical vibration of the working ball, so that the working ball can apply different static pressures with radial gradient increase to the industrial pure titanium sample. Specifically, adjusting the amplitude and frequency of the ultrasonic generator can change the amplitude and frequency of the vibration of the working ball. Preferably, the working ball is a YG6 tungsten steel ball, and the working ball is replaced regularly to ensure the stability of the rolling process.

[0088] 3) Starting a CNC lathe to perform step-by-step ultrasonic rolling processing on the surface of the industrial pure titanium sample, and continuously lubricating and cooling the surface of the industrial pure titanium sample during the step-by-step ultrasonic rolling processing, thereby obtaining an industrial pure titanium sample with a gradient nano-lamellar structure.

[0089] Specifically, under given process parameters, the industrial pure titanium sample on the CNC lathe is rotated, and the vibrating working ball is pressed into the surface of the industrial pure titanium sample with radial static pressure. At the same time, the working ball is fed along the axial direction of the industrial pure titanium sample, so that the working ball and the industrial pure titanium sample roll relative to each other, thereby forming a nanoscale or submicron lamellar structure on the industrial pure titanium sample.

[0090] Preferably, the static pressure of the ultrasonic rolling device is 800N, the feed speed of the CNC lathe is 10mm / min, and the rotation speed of the CNC lathe is greater than 700rpm.

[0091] 4) The axial cross section of the gradient nano-lamellar structure is observed using an optical microscope to obtain a microstructure image of the axial cross section of the gradient nano-lamellar structure.

[0092] 5) Based on the microstructure image of the axial cross section of the gradient nano-lamellar structure, determine the strain rate of the gradient nano-lamellar structure, and judge whether the strain rate of the gradient nano-lamellar structure is greater than or equal to a preset strain rate threshold.

[0093] The preparation conditions of gradient nanosheet structures are directly related to the strain rate in the processing technology.3 s -1 , a higher strain rate can be ensured by increasing the rotation speed of the CNC lathe.

[0094] The strain rate under this condition is verified by contradiction. The relationship between the gradient structure rheological displacement field and depth is calculated using formula (1), where y s and k are the first working condition parameters and the second working condition parameters when the static pressure of the ultrasonic rolling device is 800N and the feed speed of the CNC lathe is 10mm / min, respectively. Figure 3 Take 10 rheological curves to get y s and k are 1350μm and 0.016μm-1 respectively.

[0095] The shear displacement field can be obtained by formula (2):

[0096]

[0097] The shear strain rate can be calculated using formula (3):

[0098]

[0099] According to formula (3), it is calculated that when the diameter of the industrial pure titanium sample is R = 4000 μm and the rotation speed v1 = 700 rpm, the strain rate on the surface of the industrial pure titanium sample is about 3×10 3 s -1 , which is close to the strain rate estimated for preparing gradient nanolamellar structures in nickel. Therefore, the lathe speed for ultrasonic rolling of industrial pure titanium samples should be greater than 700 rpm. Figure 4 and Figure 5 It can be observed from the transmission electron microscope photos in that a thick and uniform lamellar structure is generated on the surface of the industrial pure titanium rod sample after ultrasonic rolling processing, which proves that the ultrasonic rolling composite strengthening method used in the present application to prepare a gradient nano-lamellar structure can effectively correct the ultrasonic rolling processing parameters.

[0100] 6) determining that the strain rate of the gradient nano-lamellar structure is greater than or equal to a preset strain rate threshold, performing surface reprocessing on the gradient nano-lamellar structure to obtain a prepared gradient nano-lamellar structure; the surface reprocessing method includes grinding and polishing such as tumbling, vibration and tumbling.

[0101] 7) Further, the fatigue life of the gradient nano-lamellar structure was tested by fatigue life test. The fatigue life test was carried out on a fatigue test platform, that is, fatigue tests were carried out on industrial pure titanium samples without surface reinforcement, industrial pure titanium samples strengthened by ultrasonic rolling, and industrial pure titanium samples treated by ultrasonic rolling composite strengthening method for preparing gradient nano-lamellar structure in this application. The fatigue test was controlled by stress, and the maximum stress value selected in the test was between 169MPa-234MPa, and the fatigue test was carried out in the order of stress value from large to small.

[0102] According to the fatigue test results, Figure 6 As shown, the fatigue life of industrial pure titanium samples treated by the ultrasonic rolling composite strengthening method for preparing gradient nano-lamellar structure in this application is greatly improved. Through verification, it is found that the ultrasonic rolling composite strengthening method for preparing gradient nano-lamellar structure in this application is simple to operate and can significantly improve the fatigue resistance of metal material samples.

[0103] It should be noted that the user information (including but not limited to user device information, user personal information, etc.) and data (including but not limited to data used for analysis, stored data, displayed data, etc.) involved in this application are all information and data authorized by the user or fully authorized by all parties, and the collection, use and processing of relevant data must comply with relevant regulations.

[0104] Those skilled in the art can understand that all or part of the processes in the above-mentioned embodiment methods can be completed by instructing the relevant hardware through a computer program, and the computer program can be stored in a non-volatile computer-readable storage medium. When the computer program is executed, it can include the processes of the embodiments of the above-mentioned methods. Among them, any reference to the memory, database or other medium used in the embodiments provided in the present application can include at least one of non-volatile and volatile memory. Non-volatile memory can include read-only memory (ROM), magnetic tape, floppy disk, flash memory, optical memory, high-density embedded non-volatile memory, resistive random access memory (ReRAM), magnetic random access memory (MRAM), ferroelectric random access memory (FRAM), phase change memory (PCM), graphene memory, etc. Volatile memory can include random access memory (RAM) or external cache memory, etc. By way of illustration and not limitation, RAM may be in various forms, such as static random access memory (SRAM) or dynamic random access memory (DRAM).

[0105] The database involved in each embodiment provided in this application may include at least one of a relational database and a non-relational database. The non-relational database may include a distributed database based on blockchain, etc., but is not limited thereto. The processor involved in each embodiment provided in this application may be a general-purpose processor, a central processing unit, a graphics processor, a digital signal processor, a programmable logic device, a data processing logic device based on quantum computing, etc., but is not limited thereto.

[0106] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0107] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and core ideas of this application. At the same time, for those skilled in the art, according to the ideas of this application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting this application.

Claims

1. An ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure, characterized in that: The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure comprises: The current metal material sample and the ultrasonic rolling strengthening device are respectively installed on a CNC lathe, and ultrasonic rolling processing parameters are set; the ultrasonic rolling processing parameters include the static pressure of the ultrasonic rolling strengthening device, the feed speed of the CNC lathe, and the rotation speed of the CNC lathe; Starting the ultrasonic generator, and adjusting the frequency of the ultrasonic generator to a preset frequency, and adjusting the amplitude of the ultrasonic generator to a preset amplitude; Starting a numerically controlled lathe to perform ultrasonic rolling processing on the surface of the current metal material sample step by step, and lubricating and cooling the surface of the current metal material sample during the ultrasonic rolling processing step by step, so as to obtain a metal material sample with a gradient nano-lamellar structure; The axial cross section of the gradient nano-lamellar structure is observed by using an optical microscope to obtain a microstructure image of the axial cross section of the gradient nano-lamellar structure; Determine the strain rate of the gradient nano-lamellar structure based on the microstructure image of the axial cross section of the gradient nano-lamellar structure, and judge whether the strain rate of the gradient nano-lamellar structure is greater than or equal to a preset strain rate threshold; If yes, the gradient nano-lamellar structure is subjected to surface reprocessing to obtain a prepared gradient nano-lamellar structure; If not, the corresponding ultrasonic rolling processing parameters are adjusted until the strain rate of the gradient nano-lamellar structure is greater than or equal to the preset strain rate threshold, and the gradient nano-lamellar structure is surface-processed to obtain a prepared gradient nano-lamellar structure.

2. The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure according to claim 1, characterized in that: The preset frequency is 20 kHz, and the preset amplitude is 16 μm.

3. The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure according to claim 1, characterized in that: The surface of the current metal material sample is subjected to ultrasonic rolling processing step by step, specifically including: The surface of the current metal material sample is subjected to step-by-step ultrasonic rolling processing using a first preset static pressure threshold and a second preset static pressure threshold in sequence; wherein the second preset static pressure threshold is greater than the first preset static pressure threshold.

4. The ultrasonic rolling composite strengthening method for preparing a gradient nano-laminated structure according to claim 3, characterized in that: The surface of the current metal material sample is subjected to multiple step-by-step ultrasonic rolling processes, and the number of step-by-step ultrasonic rolling processes is 4.

5. The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure according to claim 1, characterized in that: The preset strain rate threshold is 10 3 s -1 .

6. The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure according to claim 1, characterized in that: Based on the microstructure image of the axial cross section of the gradient nanolamellar structure, the strain rate of the gradient nanolamellar structure is determined, specifically including: Based on the microstructure image of the axial cross section of the gradient nanolamellar structure, the rheological curve is drawn; Based on the rheological curve, fitting to obtain a first operating condition parameter and a second operating condition parameter; Determining the relationship between the rheological displacement field and the depth of the gradient nano-lamellar structure based on the first operating condition parameter and the second operating condition parameter; Based on the relationship between the rheological displacement field and depth of the gradient nanolamellar structure, the shear displacement field of the gradient nanolamellar structure is determined; Based on the shear displacement field of the gradient nanolamellar structure, the strain rate of the gradient nanolamellar structure is determined.

7. The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure according to claim 6, characterized in that: The relationship between the rheological displacement field and depth of the gradient nanolamellar structure is expressed as: y(x)=y s exp(-kx); Where x is the depth of any point on the rheological curve of the gradient nanolamellar structure; y is the rheological displacement of any point on the rheological curve of the gradient nanolamellar structure; y s is the first operating condition parameter; k is the second operating condition parameter; The expression of the shear displacement field of the gradient nanolamellar structure is: γ(x)=y s kexp(kx); Where γ(x) is the shear displacement field of the gradient nanolamellar structure; The expression of strain rate of gradient nanolamellar structure is: in, is the strain rate of the gradient nanolamellar structure; R is the diameter of the current metal material sample; v1 is the rotation speed of the CNC lathe.

8. The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure according to claim 1, characterized in that: The surface reprocessing methods for gradient nano-lamellar structures include tumbling, vibrating and tumbling.

9. The ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure according to claim 1, characterized in that: Tapping oil is used as a lubricating medium and a cooling medium to lubricate and cool the surface of the current metal material sample during the step-by-step ultrasonic rolling process.

10. An ultrasonic rolling composite strengthening method for preparing a gradient nano-lamellar structure, characterized in that: The metal material sample is one of titanium, nickel, copper, iron and aluminum or an alloy formed by several of them.

Citation Information

Patent Citations

  • Ultrasonic surface rolling process nanoparticlization method and apparatus

    CN101220405A

  • Method for preparing metal heterogeneous lamellar structure based on ultrasonic rolling technology

    CN109822291A

  • Ultrasonic rolling surface layer microstructure regulation and control method

    CN111118269A

  • Ultrasonic rolling surface strengthening process for medium-entropy alloy plate

    CN112080713A

  • Manufacturing method for optimally designing mathematical model based on rolling wheel

    CN112380749A